Biosorption of Cr(VI) from aqueous solution using A. hydrophila in up-flow column: Optimization of process variables - Hasan S.H.; Srivastava P.; Ranjan D.; Talat M. (My University, 2025)
In the present study, continuous up-flow fixed-bed column study was carried out using immobilized dead biomass of Aeromonas hydrophila for the removal of Cr(VI) from aqueous solution. Different polymeric matrices were used to immobilized biomass and polysulfone-immobilized biomass has shown to give maximum removal. The sorption capacity of immobilized biomass for the removal of Cr(VI) evaluating the breakthrough curves obtained at different flow rate and bed height. A maximum of 78.58% Cr(VI) removal was obtained at bed height of 19 cm and flow rate of 2 mL/min. Bed depth service time model provides a good description of experimental results with high correlation coefficient (>0.996). An attempt has been made to investigate the individual as well as cumulative effect of the process variables and to optimize the process conditions for the maximum removal of chromium from water by two-level two-factor full-factorial central composite design with the help of Minitab ® version 15 statistical software. The predicted results are having a good agreement (R 2∈=∈98.19%) with the result obtained. Sorption-desorption studies revealed that polysulfone-immobilized biomass could be reused up to 11 cycles and bed was completely exhausted after 28 cycles. © 2009 Springer-Verlag.